2007
DOI: 10.1038/sj.bmt.1705738
|View full text |Cite
|
Sign up to set email alerts
|

Severe phimosis as a notable sequela of allogeneic stem cell transplantation in boys

Abstract: Hematopoietic SCT has improved the survival rates of patients with hematologic and metabolic disorders, as well as those with malignancy or immunodeficiency. Although various complications have been reported following allogeneic SCT, phimosis has rarely been reported, and the predisposing risk factors for phimosis have not been determined. In this study, the occurrence of severe phimosis following allogeneic SCT in boys was analyzed, and its risk factors were determined. The patients were under 15 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Phimosis is a well known manifestation of chronic graft versus host disease in male patients with hematological disease treated with allogenic bone marrow/ stem cell transplant. Suzuki et al reported phimosis in 15/46 (32.6%) uncircumcised male patients under the age of 15 years treated with allogenic stem cell transplantation (15). However, the histopathological details of the circumcision skin are not mentioned in their report.…”
Section: Discussionmentioning
confidence: 85%
“…Phimosis is a well known manifestation of chronic graft versus host disease in male patients with hematological disease treated with allogenic bone marrow/ stem cell transplant. Suzuki et al reported phimosis in 15/46 (32.6%) uncircumcised male patients under the age of 15 years treated with allogenic stem cell transplantation (15). However, the histopathological details of the circumcision skin are not mentioned in their report.…”
Section: Discussionmentioning
confidence: 85%